Legal Opinion: Perburuan Paus di Antartika (Australia v. Jepang: Intervensi Selandia Baru) - Loijens, Tasya Ester (Jurnal Hukum Lex Generalis, 2020)
In the case of Whaling in Antarctica proposed by the State of Australia, the ICJ is faced with a very technical problem relating to the interpretation and assessment of scientific elements. The court evaluated claims from Australia that Japan through a whaling program called JARPA II concealed commercial purposes behind false scientific research. This case then raised the world's attention in the international agenda, especially the correlation between law and science. On the other hand, the ICJ has also been criticized for handling cases of a technical nature, so questions arise regarding the jurisdiction of the International Court of Justice in dealing with the complexity of factual issues in a healthy and fair manner. Basically, the ICJ should avoid two main hurdles: limiting judgment only to legal aspects or becoming a science judge by conducting technical analsis and considering the position of previously handled cases. This interesting case will be analyzed by the author in relation to his studies in the perspective of international law.